Factors Associated With Length of Stay in Veterans With Inflammatory Bowel Disease Hospitalized for an Acute Flare. Issue 1 (19th December 2017) - Kelso, Michael; Weideman, Rick A; Cipher, Daisha J; Feagins, Linda A
Abstract: Background: Reducing hospital costs and risk of complications by shortening length of stay has become paramount. The aim of our study was to identify predictors and potentially modifiable factors that influence length of stay among veterans with inflammatory bowel disease admitted for an acute flare. Methods: Retrospective review of patients admitted to the Dallas VA with an acute flare of their inflammatory bowel disease between 2000 and 2015. Patients with a length of stay of ≤4 days were compared with those whose length of stay >4 days. Results: A total of 180 admissions involving 113 patients (59 with ulcerative colitis and 54 with Crohn's disease) were identified meeting inclusion criteria. The mean length of stay was 5.3 ± 6.8 days, and the median length of stay was 3.0 days. On multiple logistic regression analysis, initiation of a biologic, having undergone 2 or more imaging modalities, and treatment with intravenous steroids were significant predictors of longer lengths of stay, even after controlling for age and comorbid diseases. Conclusions: We identified several predictors for longer hospital length of stay, most related to disease severity but several of which may be modifiable to reduce hospital stays, including most importantly consideration of earlier prebiologic testing. Future studies are needed to evaluate the impact of interventions targeting modifiable predictors of length of stay on health care utilization and patient outcomes.